2018
DOI: 10.3233/cbm-181424
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long noncoding RNAs biomarkers in patients with hepatitis B virus-associated hepatocellular carcinoma

Abstract: This study identified five potential lncRNAs biomarkers for HBV-associated HCC with great diagnostic and prognostic value and provided clues for their functions in HBV-associated HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…In addition to macrophages, the functions of Tregs and fibroblasts can also be regulated by lncRNAs from tumor cells in TME. The tumor suppressor lncRNA FOXF1 Adjacent Non-Coding Developmental Regulatory RNA (FENDRR) is reported to be a favorable diagnostic biomarker for HCC (92). Microarray analysis suggested that the expression of FENDRR lncRNA in HCC samples was higher than that in the normal samples.…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
“…In addition to macrophages, the functions of Tregs and fibroblasts can also be regulated by lncRNAs from tumor cells in TME. The tumor suppressor lncRNA FOXF1 Adjacent Non-Coding Developmental Regulatory RNA (FENDRR) is reported to be a favorable diagnostic biomarker for HCC (92). Microarray analysis suggested that the expression of FENDRR lncRNA in HCC samples was higher than that in the normal samples.…”
Section: Effect Of Lncrna On Immune Cells Within Tmementioning
confidence: 99%
“…Some of these lncRNAs have been recognized as being associated with cancer. For example, C17orf82 was reported to be significantly overexpressed in HBV-related HCC [ 35 ]. LncRNA LINC01446 promotes glioblastoma progression by modulating miR-489-3p/TPT1 axis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] However, the specific molecular mechanism between the five lncRNAs and potential pathways remained unclear. Then, we identified the central genes relevant to BLCA disease.…”
Section: Discussionmentioning
confidence: 99%